Lost soul : "Confucianism" in contemporary Chinese academic discourse - Makeham, John, 1955-; Harvard-Yenching Institute (Cambridge, Mass. : Published by the Harvard University Asia Center for the Harvard-Yenching Institute : Distributed by Harvard University Press, 2008)
"Since the mid-1980s, Taiwan and mainland China have witnessed a sustained resurgence of academic and intellectual interest in ruxue - "Confucianism" - variously conceived as a form of culture, an ideology, a system of learning, and a tradition of normative values." "This study aims to show how ruxue has been conceived in academic discourse in China and Taiwan, in order to assess the achievements of this enterprise; to identify which aspects of ru thought and values academics in Taiwan and China find viable, and why; to highlight the dynamics involved in the ongoing cross-fertilization between academics in China and Taiwan made possible by this shared discourse; and to examine the relationship between these activities and cultural nationalism."--BOOK JACKET.
Pt. I. Historical Background -- 1. The Singapore Experiment and Rujia Capitalism -- 2. Developments in 1980s Taiwan and the Mainland -- 3. The Rise of Ruxue in 1990s China -- 4. Ruxue Studies in Post-1990 Taiwan -- Pt. II. Ruxue and Chinese Culture -- 5. Ruxue: The Core of Chinese Culture -- 6. Guo Qiyong, Zheng Jiadong, and Rujia Identity -- 7. Daotong and Chinese Culture -- Pt. III. The Politics of Orthodoxy -- 8. Lin Anwu's Post-New Confucianism -- 9. Ruxue: Daotong Versus Zhengtong -- 10. From Doubting Antiquity to Explaining Antiquity: Reconstructing Early Ru Intellectual History in Contemporary China -- 11. Marxism and Ruxue -- Pt. IV. Distinguishing Rujiao and Propagating Ruxue -- 12. Jiang Qing's Ruxue Revivalism -- 13. Rujiao as Religion -- 14. Popularization of Rusue and Rujia Thought and Values.
Includes bibliographical references (p. 353-391) and index.
Keywords: Confucianism -- China; Confucianism -- Taiwan